(untitled) (Vietnam Journal of Community Medicine, 2024)
Coagulation factor V is an important coagulation protein. On activation, factor V play a role of a part of prothrombinase complex which convert prothrombin to thrombin in coagulation cascade. In cell-base model, factor V is able to bind to activated platelets. So, severe factor V deficiency leads to a bleeding tendency. The acquired factor V deficiency usually presents as an autoimmune disorder and it is a rare and challenging codition to treat. It has been associated with major surgeries, antibiotics, blood transfusions, infections, autoimmune disorders, malignancy and exposure to bovine thrombin. Symptoms can range from asymptomatic to life-threatening hemorrhage with mortality rates around 15-20%. Treatment typically involves managing and preventing bleeding episodes through various strategies such as replacement therapy using fresh frozen plasma, immunosuppression therapy or bypass therapy. We describe a case of acquired factor V deficiency after recurrent choledocholithiasis surgery in which the patient developed a postoperative coagulopathy with prolonged prothrombin time and active partial thromboplastin time associated with reduced plasma factor V content and factor V inhibitor titers. The patient was successfully cured by immunosuppressive therapy including Steroids and Cyclophosphamide.